The importance of educators' role in applying the essence and principles of learning - Mufidah Zahroh; Luthfi Zufar Alfian; Nyayu Kireina Maheswari; Sri Dewi Sinta; Najwa Fakhrani (Universitas Pendidikan Indonesia, 2023)
In the education world, educators' roles must be considered. Educators are essential in directing and guiding students to achieve their best potential. This article aims to investigate and describe the vital role of educators in applying the nature and principles of learning to learn. Through this research, a deeper understanding of educators' critical role and contribution to student learning outcomes can be obtained. Researchers used the literature study method to collect and analyze relevant information about the role of educators in applying the nature and principles of learning. This research highlights the significant benefits of the educator's role in applying the essence and principles of learning. The role of educators in using the nature and principles of education is substantial. Effective educators can create exciting and meaningful learning experiences for students, adapt learning methods to suit students' needs and develop lifelong learning skills in students.